The influence of ageing on the impact damage of carbon epoxy composites - Mokhtar, Hanan; Sicot, Olivier; Rousseau, Jérôme; Aminanda, Yulfian; Aivazzadeh, Shahram (Elsevier, 2011)
This study looks into the influence of ageing on the carbon epoxy composite when impact is applied. Three different stacking sequences were investigated, one sequence with the classic lay-up, whereas the other two have quasiisotropic and quasi-homogeneous behaviour. The specimens were aged up to 2100h (3 months) in a climatic chamber with a temperature of 70°C and relative humidity of 85%. The mass was measured regularly during the hygrothermal ageing treatment. The mass was always measured directly after exiting the climatic chamber and it was noted that for each stacking sequence, the same regular increase in mass is observed until stabilisation. The specimens were then impacted and the damage was evaluated via ultrasonic analysis (C-scan). The damage due to impact was not greatly influenced by ageing, but influences the morphology of the damage in the composite